Lifestyle and Early Achievement in Families (LEAF) study: Design of an ambidirectional cohort study of prenatal marijuana exposure and child development and behaviour. Issue 6 (3rd August 2020) - Klebanoff, Mark A.; Fried, Peter; Yeates, Keith O.; Rausch, Joseph; Wilkins, Diana G.; Blei, Holly; Sullivan, Jacqueline A.; Phillips, Whitney; Wiese, Anna; Jude, Abigail; Boone, Kelly M.; Murnan, Aaron; et al.
Abstract: Background: Marijuana is the most‐used illicit substance during pregnancy in the USA, but only two cohort studies, begun over 30 years ago, were specifically established to assess the association of pregnancy use with childhood outcomes. They found use to be associated with specific deficits in executive function at 8+ years, but did not focus on these outcomes earlier in life when intervention may be more successful. Two general purpose cohorts found increased aggression in exposed female toddlers and increased behavioural problems and tic disorders in exposed school‐age children. Objectives: The Lifestyle and Early Achievement in Families (LEAF) study assesses the association of in utero marijuana exposure, documented prospectively by biomarker, self‐report, and medical records, with executive function and aggression at age 3½‐7 years. Methods: This ambidirectional cohort (historical cohort with continued follow‐up) includes women enrolled in the Perinatal Research Repository during prenatal care at Ohio State University Wexner Medical Center and their children, recontacted 3½‐7 years post‐birth. Children complete 1‐2 study visits including cognitive testing, behavioural observation, and maternal and teacher report of behaviour. Family and social environmental factors are assessed. Results: Child follow‐up began in September 2016; visits continue through August 2020. There are 362 eligible children; 32% had mothers who used marijuana during pregnancy, 10% of mothers completed college, and 23% did not complete high school. Mean maternal age at study registration in pregnancy was 26.4 years, and 63% of mothers were African American. To date, 268 children have completed at least 1 study visit. Conclusions: The LEAF Study will document the association of prenatal marijuana exposure with development and behaviour in the current era when marijuana is more potent than when previous cohorts were studied. The results may inform policy and interventions to counsel reproductive‐aged women about the risks of use during pregnancy and guide prevention and treatment of adverse effects among children.